Ekstraksi Dan Karakterisasi Pektin Dari Kulit Buah Durian (Durio Zibethinus L.) - Muhammad Khalik Habibi; Adriana Adriana (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
Albedo or durian inner skin is one of durian fruit waste and has no economic value. Durian skin proportionally contains high celluloseelements (50-60%) and lignin content (5%) and low starch content (5%) so that it can be indicated that the material can be used in themanufacture of pectin, pectin comes from Greek, pectos which means freezing or clotting. Vangueli was the first to discover the existenceof substances that can form jels derived from fruits and succeeded in isolating them as substances that can dissolve in water. In this study,durian fruit peel pectin was extracted using Microwave Assisted Extraction (MAE). This study aims to determine the amount of yieldproduced, the effect of time and temperature on yield, water content, methoxyl content, equivalent weight and functional groups. The rawmaterial source of pectin is durian fruit peel with solvent extraction method. The fixed variable used is durian fruit peel weighing 20 grams,as an acidifier used HCl solution with a concentration of 0.05 N. In this study, two independent variables were used, namely extractiontemperature 75, 80, 85, 90, 95 â„ƒ and extraction time 15, 30, 45, 60, 75 minutes. From the research results, the best results were obtainedat 60 minutes at 75 oC with 14.45% pectin yield with 9% water content. High methoxyl content was obtained at 65 oC and 45 minutes at10.08%.